Prospecção tecnológica em ligas resistentes à corrosão para aplicação no setor de Óleo e Gás - Rosa, Carlos Batista de Aguiar (Universidade Federal de São Carlos, 2014)
The steel industry is characterized by the production of metal alloys, mainly alloys based on iron and carbon. The possible combinations of alloying elements, create new arrangements or significant modifications of properties that result in special steels and high-alloy for applications in extreme situation demanding material. In this sense, the industry of high alloyed steels differs from conventional steels by a higher technological content and requires more efforts in innovation from the companies. Object of this work, Corrosion Resistant Alloys (CRAs), are part of this universe and are widely used in the Oil and Gas (O&G) industry. Investments in this sector have been significant in recent years, mainly due to new oil exploration frontiers, especially the pre-salt basis around the Brazilian coast. The materials employed in the exploration wells shall fulfill the extremely corrosive conditions which require alloys with specific characteristics to avoid the well to collapse and long term operational life. These properties are reached by specific alloy arrangements and processes. In this context, follow the materials technological development in this field can provide competitive advantage and support technology management decisions. The aim of this work was to identify technological development trends of CRAs, using technological indicators extracted from patents. The main countries owning patents have been mapped, the time course and the main steel alloys used in technological developments from the data indexed in the Derwent Innovations Index based on the period from 1960 to 2011. The results show distinct technological targets and intensity among the more patenting countries, pointing China as a major holder of patents and the United States leading new research in the area. Brazil shows an increasing trend in the number of patents, a fact explained by the importance of the country in the O&G industry. This research also indicates that much of the research of the steel industries in this sector is guided by customer needs.
Keywords: Recuperação da informação; Informação tecnológica; Indicadores de ciência e tecnologia; Siderurgia; Patentes; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA